Coral elementomes diverge for colonies persisting in vegetative lagoons versus reef environments - Emma F. Camp; David Clases; David Bishop; Annette Dowd; Samantha Goyen; Raquel Gonzalez de Vega; Paige Strudwick; David J. Suggett (Science of The Total Environment, 2025)

Early-stage outcomes and cost-effectiveness of implementing tourism-led coral propagation and outplanting in the Whitsundays (Great Barrier Reef) - Rachael Scott; David Suggett; Cassidy Hayward; Brent Chatterton; John Edmondson; Johnny Gaskell; Gemma M. Gillette; Lorna Howlett; Emily Monacella; Christine D. Roper; Paige Strudwick; James Unsworth; et al. (Frontiers in Marine Science, 2024)
Implementation of coral restoration practices within reef management strategies is accelerating globally to support reef resilience and recovery. However, full costs underpinning restoration project feasibility have historically been underreported yet are critical to informing restoration cost-benefit decision-making. Such knowledge is especially lacking for Australia’s Great Barrier Reef (GBR), where a coral restoration program led by reef tourism operators, Coral Nurture Program (CNP), was initiated in 2018 (northern GBR) and continues to scale. Here we describe the early outcomes and costs of implementing similar tourism-led asexual coral propagation and outplanting practices in a new region, the Whitsundays (central GBR) through the CNP. Specifically, we detail the local operational and environmental context of CNP Whitsundays, describe the costs of implementation and continuation of restoration activities, as well as evaluate survivorship of coral outplants across three restoration sites for nine months after project establishment (August 2022 to June 2023). Baseline benthic surveys revealed relatively low hard coral cover at restoration sites (ranging from 3.22-8.67%), which significantly differed in benthic composition from coral collection sites (ranging 16.67-38.06%), supporting strong motivation by tourism operators to undertake restoration activities. Mean coral survivorship of coral outplants in fate-tracked plots differed between the three restoration sites after 267 days (ranging 23.33-47.58%), with declines largely driven by coral detachment. Early-stage cost-effectiveness (costs relative to outplant survival) associated with implementation of restoration activity varied widely from US$33.04-178.55 per surviving coral (n = 4,425 outplants) depending on whether ‘in-kind’ costs, restoration activity (outplanting only vs. total costs encompassing planning through to monitoring), site-based survivorship, or a combination of these factors, were considered. As coral reef restoration projects continue to be established globally, our results highlight the need for ongoing, long-term monitoring that can inform adaptive practice, and fully transparent cost-reporting to understand and improve feasibility for any given project. We further highlight the inherent context-dependency of restoration costs, and the importance of considering local social-environmental contexts and their associated cost-benefits in economic rationale for reef restoration projects.

Population and clonal structure of Acropora cf. hyacinthus to inform coral restoration practices on the Great Barrier Reef - Lorna Howlett; Emma F. Camp; Nicolas S. Locatelli; Iliana B. Baums; Paige Strudwick; Sage Rassmussen; David J. Suggett (Coral Reefs, 2024)
A key goal of coral restoration is to re-establish self-sustaining coral populations and ensure resilience to future stressors, which requires that genetic diversity is maximised. However, coral genetic and genotypic (clonal) diversity is variable across reef sites via success of sexual recruitment, and cryptic species diversity can complicate breeding efforts. Assessing genotypic and genetic diversity of colonies to be used in restoration is therefore critical to avoid founder, inbreeding or outbreeding effects. Considering recent efforts to upscale coral propagation on the Great Barrier Reef (GBR), we examined species, population and clonal structure of a commonly out-planted tabular Acropora species— Acropora hyacinthus (Dana, 1864). A total of 189 colonies were sampled from six reef systems throughout the northern-central GBR and genotyped using an Acropora- specific Affymetrix microarray, which resulted in 1387 variant sites that passed quality control. Cryptic species were readily resolved and all sampled A. hyacinthus colonies represented unique genotypes within sites at three reefs. At reefs that contained multi-ramet genets (clonal genotypes), the mean and maximum between-ramet distances were 0.68 and 1.99 m, respectively. Therefore, sampling colonies > 2 m apart increases the likelihood these colonies represent distinct genets. Such a sampling design therefore maximises genotypic diversity when sourcing colonies for propagation and out-planting. Based on these variant sites, we found no between-reef genetic divergence based on locality. Furthermore, through unintentional sampling of non-target tabular Acroporid species, we show how this genotyping method may be used for resolving taxonomic uncertainty as well as population dynamics.

Assessing how metal reef restoration structures shape the functional and taxonomic profile of coral-associated bacterial communities - Paige Strudwick; David J. Suggett; Justin R. Seymour; Matthew Z. DeMaere; Amanda Grima; John Edmondson; Alicia McArdle; Freda Nicholson; Emma F. Camp (Frontiers in Marine Science, 2024)
Significant threats to the long-term persistence of coral reefs have accelerated the adoption of coral propagation and out-planting approaches. However, how materials commonly used for propagation structures could potentially affect coral-associated bacterial communities remains untested. Here, we examined the impact of metal propagation structures on coral-associated bacterial communities. Fragments of the coral species Acropora millepora were grown on aluminium, sand/epoxy-coated steel (Reef Stars), and uncoated steel (rebar) structures. After 6 months, the functional and taxonomic profiles of coral-associated bacterial communities of propagated corals and reef colonies were characterised using amplicon (16S rRNA gene) and shotgun metagenomic sequencing. No differences in the phylogenetic structure or functional profile of coral-associated bacterial communities were observed between propagated corals and reef colonies. However, specific genes and pathways (e.g., lipid, nucleotide, and carbohydrate metabolism) were overrepresented in corals grown on different materials, and different taxa were indicative of the materials. These findings indicate that coral propagation on different materials may lead to differences in the individual bacterial taxa and functional potential of coral-associated bacterial communities, but how these contribute to changed holobiont fitness presents a key question to be addressed.

Bacterial communities associated with corals out-planted on the Great Barrier Reef are inherently dynamic over space and time - Paige Strudwick; Justin Seymour; Emma F. Camp; Christine Roper; John Edmondson; Lorna Howlett; David J. Suggett (Marine Biology, 2023)
Coral propagation and out-planting are becoming commonly adopted as part of reef stewardship strategies aimed at improving reef resilience through enhanced natural recovery and rehabilitation. The coral microbiome has a crucial role in the success of the coral holobiont and can be impacted shortly after out-planting. However, long-term characterisation of the out-plant microbiome in relation to out-plant survival, and how these properties vary across reef sites, is unexplored. Therefore, at three reef sites on Opal Reef, Great Barrier Reef (Mojo, Sandbox and Rayban, 16°12′18″S 145°53′54″E), we examined bacterial communities associated with out-planted Acropora millepora coral and monitored coral survival over 12 months (February 2021–22). Bacterial communities of out-planted corals exhibited significant changes from donor colonies 7 days to 1.5 months after out-planting. Further, bacterial community composition differed for sites Sandbox and Rayban with low overall survival (0–43%) versus Mojo with higher overall survival (47–75%). After initial dissimilarity in bacterial communities of out-plants across sites at 1.5 months, and despite changes within sites over time, out-plants exhibited similar microbial communities across sites at 7 days and 6, 9 and 12 months. We hypothesise these trends reflect how bacterial communities are shaped by rapid changes in local environmental characteristics (e.g. from source to out-planting site), where out-plant bacterial communities ‘conform’ to out-planting site conditions. After initial changes, out-plant bacterial communities may then be under the influence of global environmental conditions—such as annual trends in temperature across seasons. Such outcomes indicate the importance of site selection in shaping initial coral bacterial communities and subsequent out-plant success. Importantly, continued differences in out-plant survival trajectory but similar bacterial communities across sites after 1.5 months indicate that other factors—apart from bacterial community changes—likely govern out-plant success in the longer term. Our research highlights the need to resolve drivers of small-scale site differences alongside higher resolution spatiotemporal monitoring of environmental conditions to distinguish key drivers of (i) microbial change during out-planting and (ii) out-plant survival to subsequently inform out-plant site selection to optimise future restoration efforts.

Physiological factors facilitating the persistence of Pocillopora aliciae and Plesiastrea versipora in temperate reefs of south-eastern Australia under ocean warming - Raúl A. González-Pech; David J. Hughes; Paige Strudwick; Brett M. Lewis; David J. Booth; Will F. Figueira; Brigitte Sommer; David J. Suggett; Jennifer Matthews (Coral Reefs, 2022)
High-latitude reefs are suboptimal coral habitats, but such habitats are increasingly considered to be potential refugia from climate change for range-shifting coral reef species. Notably, tropical reef fish have been observed along the south-east coast of Australia, but their establishment on temperate rocky reefs is currently limited by winter minimum temperatures and other resource needs, such as structurally complex habitats typical of tropical reefs. Recent expansion of the branching subtropical coral Pocillopora aliciae in rocky reefs near Sydney (34° S) could diversify the architectural structure of temperate marine environments, thereby providing potential shelter for tropical reef taxa in warming seas. Here, we investigated whether future environmental conditions ( i.e. temperature increase) can influence the dominance of the subtropical branching coral P. aliciae over the resident encrusting coral Plesiastrea versipora in coastal Sydney by characterising physiological ( e.g. metabolic stability) and behavioural ( e.g. interspecific competitive hierarchy) traits that contribute to their competitive fitness. Our results suggest that a metabolic response, mediated by sterol and lipid metabolic pathways and provision of antioxidants, allows P. aliciae to reduce cellular stress and withstand exposure to short-term increased temperature. Conversely, P. versipora was more susceptible to heat exposure with no metabolic mediation observed. While P. versipora displayed greater aggressive behaviour when in direct contact with P. aliciae under all temperature conditions, the superior physiological and metabolic flexibility under increased temperatures of P. aliciae suggests that this species will likely outperform P. versipora under future increased temperatures. Such contrasting responses to environmental change would facilitate shifts in coral community and functional composition that could support further tropicalisation of coastal New South Wales.

Correction to: Impacts of nursery-based propagation and out-planting on coral-associated bacterial communities - Paige Strudwick; Justin Seymour; Emma F. Camp; John Edmondson; Trent Haydon; Lorna Howlett; Nine Le Reun; Nahcshon Siboni; David J. Suggett (Coral Reefs, 2022)

Impacts of nursery-based propagation and out-planting on coral-associated bacterial communities - Paige Strudwick; Justin Seymour; Emma F. Camp; John Edmondson; Trent Haydon; Lorna Howlett; Nine Le Reun; Nahcshon Siboni; David J. Suggett (Coral Reefs, 2022)